The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1983-21252017v30n117rc
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physical Attributes and Yield of Winter Common Bean Crop Under a No-Till System in the Brazilian Cerrado

Abstract: -Knowledge of the interactions between soil physical properties and yield performance in agricultural crops is very important for the adoption of appropriate management practices. This study aimed to evaluate the linear and spatial correlations between some soil physical attributes, straw production in the palisade grass (Urochloa brizantha), and grain yield of winter common bean in succession to the grass under an irrigated no-till system in an Oxisol Haplorthox in the Cerrado lowlands region of Brazil. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
(15 reference statements)
1
7
0
7
Order By: Relevance
“…Therefore, bean grain yield (GY) presented a very high variation coefficient (31.3%). Montanari et al [14] and Silva et al [5], when analyzing a dystroferric Red Latosol under no-tillage in regular meshes of 117 and 124 sampling points, found high variability for bean grain yield (21.1% and 22.2%, respectively). In this aspect, Montanari et al [7] found different values, mean variability (18.3%), when evaluating bean culture under the same conditions.…”
Section: Fig 2 Climatic Data Of Temperatures and Precipitations In mentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, bean grain yield (GY) presented a very high variation coefficient (31.3%). Montanari et al [14] and Silva et al [5], when analyzing a dystroferric Red Latosol under no-tillage in regular meshes of 117 and 124 sampling points, found high variability for bean grain yield (21.1% and 22.2%, respectively). In this aspect, Montanari et al [7] found different values, mean variability (18.3%), when evaluating bean culture under the same conditions.…”
Section: Fig 2 Climatic Data Of Temperatures and Precipitations In mentioning
confidence: 98%
“…In this context, a geostatistical method can be used as a tool to evaluate the spatial variability of soil and plant properties through a simple semivariogram and kriging process to estimate values at different locations. This approach is appropriate to analyze properties whose variability has a certain organization degree expressed by spatial dependence [5].…”
Section: Introductionmentioning
confidence: 99%
“…KEYWORDS: Availability, fertility, soil. (RAMOS et al, 2015;BEUTLER et al, 2016;FERREIRA et al, 2016;OLIVEIRA et al, 2016;SILVA et al, 2016;TEIXEIRA et al,2016;SILVA et al, 2017 No local de estudo foram selecionadas cinco áreas distintas, limítrofes, sob as mesmas condições topográfi cas e edafoclimáticas (mesmo solo e clima, textura média, relevo plano), diferenciando-se apenas no uso e manejo adotado. As áreas avaliadas foram: A1 sob mata nativa não disturbada; a A2 área com culturas anuais;…”
Section: Diagnosis Of the Phosphorus And Ph Phosphorus In Representatunclassified
“…O feijoeiro (Phaseolus vulgaris) é uma das principais culturas cultivadas no Brasil, produtiva durante todo o ano em diferentes condições edafoclimáticas, sem restrições durante o desenvolvimento da planta (SIMPLÍCIO et al, 2016;SILVA et al, 2017). O maior País produtor mundial de feijão-comum é o Brasil, estando em segundo lugar Minas Gerais com 15% da produção nacional; é importante ressaltar que a produção nacional gira em torno de 3,4 milhões de toneladas, com produtividade média de 852 kg ha -1 , este valor quando comparado ao potencial produtivo das cultivares, ainda é considerado baixo (PAULA JÚNIOR et al, 2008;MARTINS et al, 2009).…”
Section: Introductionunclassified
“…Uma estratégia de manejo específica pode ser evidenciada pelos fatores físicos do solo que incluem o teor de água, sistema de armazenamento, aeração e os impedimentos mecânicos presentes no solo os quais dificultam o desenvolvimento das raízes, e podem ser reduzidos pelo conhecimento dos atributos físicos do solo e das cultivares de feijão utilizada em busca de aperfeiçoar e melhorar a produtividade agrícola (CARVALHO et al, 2006;SILVA et al, 2017).…”
Section: Introductionunclassified